2019
DOI: 10.1080/21655979.2019.1679698
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus circRNAome as host miRNA sponge regulates virus infection, cell cycle, and oncogenesis

Abstract: Epstein-Barr virus (EBV) is an oncogenic virus that infects more than 90% of the world's population. The proteins and miRNAs encoded by EBV are involved in multiple human malignancies. Recently R-resistance RNA-seq demonstrated that EBV-encoded circular RNAs. The current research aims to explore their functions in EBV-associated malignancies. Total 56 miRNAs were sponged by circRNAome. 24 and 9 in EBV host B and epithelial cells out of 56 miRNAs were detectable by miRNAseq. 18 and 5 miRNAs were down-regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 57 publications
(72 reference statements)
0
24
0
Order By: Relevance
“…Host miRNAs constitute ~0.01% of total cellular and tissue RNA ( 81 ), while the viral RNA in infected lung cells can reach more than 50% of total cellular RNA ( 13 ). Furthermore, evidence that viral RNA sponges are capable of being efficient in removing host miRNAs is demonstrated in studies on Epstein-Barr virus which illustrates that EBV miRNA sponges regulate virus infection as well as oncogenesis by downregulating a number of target miRNAs ( 85 ). Viral RNA sponge activity has also been reported for Herpes virus ( 15 ) and hepatitis C virus ( 64 ).…”
Section: Comparison Of the Mirna Target Sites In Human Coronavirusesmentioning
confidence: 99%
“…Host miRNAs constitute ~0.01% of total cellular and tissue RNA ( 81 ), while the viral RNA in infected lung cells can reach more than 50% of total cellular RNA ( 13 ). Furthermore, evidence that viral RNA sponges are capable of being efficient in removing host miRNAs is demonstrated in studies on Epstein-Barr virus which illustrates that EBV miRNA sponges regulate virus infection as well as oncogenesis by downregulating a number of target miRNAs ( 85 ). Viral RNA sponge activity has also been reported for Herpes virus ( 15 ) and hepatitis C virus ( 64 ).…”
Section: Comparison Of the Mirna Target Sites In Human Coronavirusesmentioning
confidence: 99%
“…However, the reason why miR-187 inhibits cell proliferation of NSCLC remains to be investigated. Overall, aberrant cell cycle regulation is likely to be an important factor [35]. Indeed, subsequent cell cycle analyses in the present study revealed that A549 and SPC-A-1 cells that were transfected with miR-187 mimic had an evident cell cycle arrest at the G0/G1 phase.…”
Section: Discussionmentioning
confidence: 50%
“…Using a R-resistance RNA-seq, EBV-encoded circRNAs have been investigated. They identified the miRNAs sponged by EBV-encoded circRNAs and their interactions with target mRNAs, which regulate the EBV replication and its related tumorigenesis ( Qiao et al, 2019 ). It has been shown that KSHV infection increased hsa_circ_0001400 expression level in HUVECs cells.…”
Section: Circrnas Regulate Viral Replication and Induce Antiviral Immmentioning
confidence: 99%